Medical aid arrangements for arterial hypertension patients in the areas of Irkutsk Region which were characterized by low accessibility of specialized medical aid - A. V. Sinkov; G. M. Sinkova (Бюллетень сибирской медицины)
The complex of medical aid arrangements for arterial hypertension patients in the rural and farthest areas of Irkutsk Region which were characterized by low accessibility of specialized medical aid was developed. The complex make possible to improve awareness, treatment and control of arterial hypertension.